An Introduction to the Hadith - Burton, John (Edinburgh University Press, 1994)
This is a clear introduction to the arguments surrounding both the Hadith and the documents themselves. Comparing the views put forward in the Hadith with those of the Qur'an, it takes the student through all aspects of the Hadith in clear and accessible terms.